PEMETAAN NILAI SUSEPTIBILITAS MAGNETIK PASIR PANTAI GANDORIAH PARIAMAN SUMATERA BARAT - Putri Vanera Puspita; Erwin Erwin (Komunikasi Fisika Indonesia, 2020)
Mapping of magnetic susceptibility values of sand of  Gandoriah beach, Pariaman West Sumatera has been carried out. The composition of sand beach was identified using X-Ray Fluorescence Spectroscopy (XRF) and the map of  magnetic susceptibility and mass susceptibility of the sample were determined using Software Surfer 11. The samples were collected based on grid technique from 25 points location. The separation between magnetic particles and nan magnetic particles was done using iron sand separator for 1 time process.The result of the calculation of the magnetic degree of the sample using Iron Sand Separator for 1 time prosess showed that the values are in the range of 3,88 %-5,12 %. Magnetic and mass susceptibility values of the sample are in the range of (603,3-1351,46)×10-5 and (112,76–1086,85)×10-8 m3/Kg respectively. Magnetic and mass susceptibility of the concentrate (product of iron sand separator) are in the range of (1367,55–2155,9)×10-5 and (927,41–1774,28)×10-8 m3/Kg respectively. These values are in the range of Ilminate mineral that is (220-380000)×10-5 and (46-80000)×10-8 m3/Kg respectively. The percentage of Fe and Ti increases from  6,276 % to  54,549 % and from  0,441% to 5,102% respectively after being processed by iron sand separator. The results also showed that magnetic susceptibility values increase toward the sea water.